Biocomposite Hydrogels for the Treatment of Bacterial Infections: Physicochemical Characterization and In Vitro Assessment - Delia Mihaela Rata; Anca Niculina Cadinoiu; Marcel Popa; Leonard Ionut Atanase; Oana Maria Daraba; Irina Popescu; Laura Ecaterina Romila; Daniela Luminita Ichim (Pharmaceutics, 2021)
Hydrogels based on natural and synthetic polymers and inorganic nanoparticles proved to be a viable strategy in the fight against some Gram-positive and Gram-negative bacteria. Additionally, numerous studies have demonstrated the advantages of using ZnO nanoparticles in medicine due to their high antibacterial efficacy and relatively low cost. Consequently, the purpose of our study was to incorporate ZnO nanoparticles into chitosan/poly (vinyl alcohol)-based hydrogels in order to obtain a biocomposite with antimicrobial properties. These biocomposite hydrogels, prepared by a double crosslinking (covalent and ionic) were characterized from a structural, morphological, swelling degree, and mechanical point of view. FTIR spectroscopy demonstrated both the apparition of new imine and acetal bonds due to covalent crosslinking and the presence of the sulfate group following ionic crosslinking. The morphology, swelling degree, and mechanical properties of the obtained hydrogels were influenced by both the degree of covalent crosslinking and the amount of ZnO nanoparticles incorporated. In vitro cytotoxicity assessment showed that hydrogels without ZnONPs are non-cytotoxic while the biocomposite hydrogels are weak (with 3% ZnONPs) or moderately (with 4 and 5% ZnONPs) cytotoxic. Compared to nanoparticle-free hydrogels, the biocomposite hydrogels show significant antimicrobial activity against S. aureus, E. coli, and K. pneumonia.